Asymptomatic Hepatocellular Carcinoma (Clinical Case) - A. S. Shkaraburov; D. N. Rudenko; E. F. Vaiman; O. M. Soboleva; Yu. V. Zakharova (Креативная хирургия и онкология)
Introduction. Hepatocellular carcinoma is oft en asymptomatic in its early stages and when the tumor is small. Though this type of tumor is oft en accompanied with metastasis to the lungs, the present paper describes a patient whose both pathologies were accidentally detected by a chest X-ray. According to his medical history, the last abdominal ultrasound was carried out three years ago.The aim of this paper is to present a clinical case which demonstrates the asymptomatic primary cancer with pulmonary metastases and the diagnostic potential of radiological methods.Materials and methods. During a chest X-ray, pensioner K, aged 65, was found to have a circular shadow of 2.5 cm in diameter in bronchopulmonary segment IV of the right lung. During the outpatient stage, the patient underwent clinical and laboratory diagnosis as well as ultrasound examination of the thyroid gland, abdominal, retroperitoneal and pelvic organs.Results and discussion. Based on the data of histological and immunohistochemical examination, the diagnosis of «poorly differentiated hepatocellular carcinoma» was made. The paper presents a clinical case of hepatocellular carcinoma as an accidental finding against the background of the absence of complaints, clinical picture and characteristic changes in clinical and laboratory diagnostics. The paper highlights the importance of the primary (outpatient) healthcare activity aimed at working with the senior population for early detection of malignant pathology, including HCC.Conclusion. The patient is scheduled for surgery and chemotherapy. The case follow-up showed a successful outcome.